The spatial-temporal consistency of chlorophyll-a and fishery resources in the water of the Zhoushan archipelago revealed by high resolution remote sensing - Cai, Lina; Tang, Rong; Yan, Xiaojun; Zhou, Yongdong; Jiang, Jingjing; Yu, Menghan (Frontiers in Marine Science, 2022)
Details of the chlorophyll-a (Chl-a) distribution in the water of the Zhoushan archipelago were analyzed based on data from the panchromatic multispectral sensor (PMS) of the GaoFen-6 (GF-6). A new Chl-a inversion model was built using in-situ Chl-a and the green-red bands of the 2 m spatial resolution GF-6/PMS image. Combined with fishery data, the relationship between Chl-a concentration and fish resources were revealed. The results show that: (1) High Chl-a concentration area was mainly concentrated in the nearshore intensive islands waters, and Chl-a concentration changes obviously with the change of tidal currents. Chl-a concentration around islands increases, especially downstream of islands. Seasonally, Chl-a concentration is higher in spring and summer, lower in autumn, and lowest in winter. (2) The change of fish eggs and larvae in the water of the Zhoushan archipelago shows consistency with the spatial distribution and seasonal variation of Chl-a. (3) The interaction between tidal currents and islands results in the diverse currents (upstream upwelling and downstream vortex currents) around the islands, promoting vertical water exchange and the uplifting of nutrients, resulting in a high overall Chl-a concentration in the waters around the islands. The diverse flow conditions, the ideal nutrient-rich environment, and the abundant phytoplankton attract a large number of fish to gather and breed in the waters around the islands. (4) Chl-a of intensive island waters is an essential indicator for fish spawning grounds.